THE RELATIONSHIP BETWEEN THE SEVERITY OF MALOCCLUSION AND GINGIVAL STATUS IN STUDENTS OF SMPN 5 MARABAHAN - Akhmad Aufayed Ma’rifatullah; Diana Wibowo; Aulia Azizah (Dentino : Jurnal Kedokteran Gigi, 2021)
ABSTRACTBackground: South Kalimantan experienced dental and mouth problems with a prevalence of 59,6%, so did Barito Kuala Regency with 68,66%. Malocclusion is a dental and oral health problem related to the disharmony between jaws and teeth. Many cases of malocclusion occur in children aged 12-14 years by 15,6% in the form of crowded teeth in South Kalimantan. Malocclusion is a factor that can cause food debris to stick to the interdental area between the crowded teeth, thus forming plaque accumulation. Plaque is the primary etiological factor that influences gingival status. Objective: This study aimed to determine the relationship between the severity of malocclusion and gingival status in students aged 12-14 years at SMPN 5 Marabahan. Method:  This study used analytic survey research with cross sectional research design. The research population was all students of SMPN 5 Marabahan aged 12-14 years who born in March 2005 - January 2008, amounting to 88 people. The minimum sample size which determined by the proportion estimation formula was 47 people. The used sampling technique was simple random sampling technique with inclusion and exclusion criteria. Results: The distribution frequency of the study showed mild malocclusion of 55,3% and mild inflammation of 57,4%. Spearman analysis test results on the severity of malocclusion based on Mal I and gingival status based on GI showed a significance value of p = 0,045 (p < 0,05). Conlclusion: It could be concluded that there was a relationship between the severity of malocclusion and gingival status in students aged 12-14 years at SMPN 5 Marabahan.Keywords:Gingival Index, Gingival Status, Malalignment Index, Malocclusion, Permanent Tooth Occlusion Stage 2.